Relationship between cognitive dysfunction and urinary 8-OHdG levels in children with obstructive sleep apnea - Chen, Bolin; Ji, Jiapeng; Lv, Meng; Xu, Xueyun; Wang, Yuqing (Frontiers in Neurology, 2025)
BackgroundObstructive sleep apnea (OSA) is a condition characterized by partial or complete obstruction of the upper respiratory tract during sleep, which can result in neurocognitive deficits and cognitive dysfunction in children. Oxidative stress may play a significant role in OSA-related disorders, with 8-hydroxy-2′-deoxyguanosine (8-OHdG) serving as a primary marker of oxidative DNA damage for assessing oxidative stress levels. This study aims to investigate the relationship between urinary 8-OHdG levels in children with OSA and cognitive dysfunction.MethodsThe study included children with habitual snoring from April 2023 to June 2024 at the Children’s Hospital of Soochow University. All participants completed the PedsQL questionnaire and underwent polysomnography (PSG) assessment and urine collection for 8-OHdG analysis.ResultsIn total, 99 children with OSA and 35 children with non-OSA were included. The urinary 8-OHdG levels were higher in the OSA group (240.94 ± 11.51 pg./mL) than in the non-OSA group (230.73 ± 13.82 pg./mL) (p < 0.001). Moreover, 8-OHdG was correlated with the course of the disease, obstructive apnea–hypopnea index, minimum arterial oxygen saturation (SaO2), average SaO2, oxygen desaturation index, and cognitive dysfunctions evaluated by the PedsQL questionnaire (all p < 0.05). The area under the receiver operating characteristics curve of 8-OHdG was 0.661 (95%confidence interval, 0.550–0.773). Binary logistic regression analysis revealed that 8-OHdG was significantly associated with the School Functioning score (p = 0.004).ConclusionUrinary 8-OHdG may serve as a non-invasive, objective biomarker for assessing cognitive dysfunctions in children with OSA.